2022
DOI: 10.1021/acs.jpca.2c04455
|View full text |Cite
|
Sign up to set email alerts
|

OH Radical and Chlorine Atom Kinetics of Substituted Aromatic Compounds: 4-Chlorobenzotrifluoride (p-ClC6H4CF3)

Abstract: The mechanisms for the OH radical and Cl-atom gas-phase reaction kinetics of substituted aromatic compounds remains a topic of atmospheric and combustion chemistry research. 4chlorobenzotrifluoride (para-chlorobenzotrifluoride, p-ClC6H4CF3, PCBTF) is a commonly used substituted aromatic volatile organic compound (VOC) in solvent-based coatings. As such, PCBTF is classified as a volatile chemical product (VCP) whose release into the atmosphere potentially impacts air quality. In this study, rate coefficients, k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Both apparatuses have been used in the past and only brief descriptions of the experimental setups and methods are given herein. [15][16][17][18] 2.1 Chamber relative rate measurements: THALAMOS THALAMOS consists of three main components, (i) a cuboid Teflon reactor, 0.6 m 3 , housed in a climatic thermostatic cage (climatic box VT-4100, Vötsch industrietechnik, Germany) providing temperature regulation between 231 and 453 K, (ii) a set of 10 UV-A (PL-L 24 W/10/4P, Philips, Netherlands), and 10 UV-C (HNS-L 24 W 2G11, Osram, UK) photolysis lamps, equally spaced around the Teflon chamber inside the climatic box and (iii) FTIR and SIFT-MS detection setups.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both apparatuses have been used in the past and only brief descriptions of the experimental setups and methods are given herein. [15][16][17][18] 2.1 Chamber relative rate measurements: THALAMOS THALAMOS consists of three main components, (i) a cuboid Teflon reactor, 0.6 m 3 , housed in a climatic thermostatic cage (climatic box VT-4100, Vötsch industrietechnik, Germany) providing temperature regulation between 231 and 453 K, (ii) a set of 10 UV-A (PL-L 24 W/10/4P, Philips, Netherlands), and 10 UV-C (HNS-L 24 W 2G11, Osram, UK) photolysis lamps, equally spaced around the Teflon chamber inside the climatic box and (iii) FTIR and SIFT-MS detection setups.…”
Section: Methodsmentioning
confidence: 99%
“…The uncertainty in thermochemistry calculations is estimated to be less than 5 kJ mol −1 for the studied reactions. 16 Yuan et al 29 have previously theoretically studied the kinetics and the reaction mechanism for reaction 1. In our thermochemical approach the reaction pathways enthalpy, entropy and free energy, ΔH, ΔS and ΔG, were calculated as a function of temperature to evaluate the OH-furan adduct thermodynamic stability over the temperature range of the present kinetic measurements and determine that our measured k 1 (T) values correspond to the forward rate coefficient.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Initiation of the VOC oxidation process is primarily driven by the sunlight-derived OH radical but also via reactions involving other oxidants. Papers in this virtual special issue include studies of the initiation reactions of VOC species by OH, Cl, O 3 , , NO 3 , and HCO, as well as by direct photolysis . Chamber studies, in which the products of a VOC oxidation process are identified and quantified, are also prevalent; two studies quantify the formation of secondary organic aerosol (SOA) in the reaction of OH or NO 3 with monoterpenes, , while a combined experimental/theoretical study shows that methylmethanimine oxidation via the OH radical is unlikely to compete with atmospheric hydrolysis of this species .…”
mentioning
confidence: 99%